The Implementation of Technology in EFL Classroom Activity - Safitri, Baiq Wimandari; Lalu Muhammad Ridho Firmansyah; Juniarly, Lalu Anugrah Dimas (INGGARA (Jurnal Pendidikan Bahasa Inggris dan Bahasa Arab), 2024)
This study aims to show and describe which technology is used in schools. By using qualitative methods and observation, the data were gathered and analyzed using technology theories. The results of the study are the application of technology is applied in-class activity related to EFL such as technology as a tool or teaching media and technology as the environment of the teaching and learning process.